Resistance-resistant antibacterial treatment strategies - Batchelder, Jonathan I.; Hare, Patricia J.; Mok, Wendy W. K. (Frontiers in Antibiotics, 2023)
Antibiotic resistance is a major danger to public health that threatens to claim the lives of millions of people per year within the next few decades. Years of necessary administration and excessive application of antibiotics have selected for strains that are resistant to many of our currently available treatments. Due to the high costs and difficulty of developing new antibiotics, the emergence of resistant bacteria is outpacing the introduction of new drugs to fight them. To overcome this problem, many researchers are focusing on developing antibacterial therapeutic strategies that are “resistance-resistant”—regimens that slow or stall resistance development in the targeted pathogens. In this mini review, we outline major examples of novel resistance-resistant therapeutic strategies. We discuss combination therapies that aim to sabotage mutagenic defensive mechanisms and eliminate potentially resistant pathogens by combining current antibiotics with other therapeutics, such as antibodies or phages. We examine the effectiveness of antibiotic cycling and evolutionary steering, in which a bacterial population is forced by one antibiotic toward susceptibility to another antibiotic. We also consider the use of compounds that reduce mutagenesis and thereby decrease the likelihood of resistance emergence. Finally, we highlight promising future directions in this field, including the potential of applying machine learning and personalized medicine to fighting antibiotic resistance emergence and out-maneuvering adaptive pathogens.